Implementasi Jiwa Inovatif Pedagang pada Objek Wisata Situ Tandon Ciater, Kota Tangerang Selatan - Kurniawaty, Erlita; Nani, Nani; Furyanah, Anah (Indonesian Journal of Society Engagement, 2023)
In community service activities, we explored the implementation of an innovative spirit in tourist traders in Tandon Ciater, South Tangerang City. The background involves the challenges faced by local traders in dealing with dynamic changes in the tourism industry. Our main objective is to understand the extent to which traders in Tandon Ciater implement innovation in their business practices and its impact on the tourist experience. Through a qualitative approach, we investigate traders' efforts in developing new products and services, as well as innovative strategies in marketing and business management. The results of community service activities show that traders who adopt an innovative spirit experience significant increases in competitiveness and income. They successfully identify local market opportunities, respond to changing tourism trends, and create unique experiences for visitors. In this context, innovation is not only limited to physical products, but also includes the use of technology to improve service and communication with customers. In conclusion, the application of an innovative spirit to tourist traders in Tandon Ciater can be a valuable model for developing the local economy and increasing the attractiveness of tourist destinations. Therefore, innovative development efforts need to be supported and are not sufficient to encourage sustainable growth in the tourism sector.